Academic Procrastination among College Students: Do Learning Awareness and Self-Management Play a Role? - Rahayu, Widya; Candra, Hadi; Sujadi, Eko (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Academic procrastination is a prevalent tendency among students. This study examines the impacts of learning awareness and self-management on academic procrastination. Employing a quantitative survey approach, the research involved 134 Kerinci State Islamic Institute students in Jambi Province, selected through convenience sampling. Descriptive analysis was conducted to assess the levels of each variable. Findings suggest a low level of academic procrastination, with learning awareness and self-management exhibiting moderate levels. Hypothesis testing demonstrates that learning awareness and self-management significantly influence academic procrastination individually and concurrently. Future research endeavors should construct a more intricate structural model by incorporating additional variables that directly or indirectly impact academic procrastination.